2020
DOI: 10.1186/s12864-020-06796-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diversity in pearl millet inbred lines derived from landraces and improved varieties

Abstract: Background: Genetic improvement of pearl millet is lagging behind most of the major crops. Development of genomic resources is expected to expedite breeding for improved agronomic traits, stress tolerance, yield, and nutritional quality. Genotyping a breeding population with high throughput markers enables exploration of genetic diversity, population structure, and linkage disequilibrium (LD) which are important preludes for marker-trait association studies and application of genomic-assisted breeding. Results… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
5
12
2
Order By: Relevance
“…Similar results regarding effectiveness of SSR markers in monitoring genetic diversity have also been reported by other investigators [12,15,27,[29][30][31]. Several reports have been observed on estimation of genetic diversity among parental lines of pearl millet on the basis of molecular profiling [14,15,16,11,17,27]. But, this study is the first report on molecular characterization and genetic diversity analysis of hybrids and varieties which will provide molecular database for the existing hybrids and varieties and will be helpful for developing genomic studies and DNA fingerprinting for pearl millet hybrids and varieties.…”
Section: Molecular Characterization and Ssr Analysissupporting
confidence: 84%
See 3 more Smart Citations
“…Similar results regarding effectiveness of SSR markers in monitoring genetic diversity have also been reported by other investigators [12,15,27,[29][30][31]. Several reports have been observed on estimation of genetic diversity among parental lines of pearl millet on the basis of molecular profiling [14,15,16,11,17,27]. But, this study is the first report on molecular characterization and genetic diversity analysis of hybrids and varieties which will provide molecular database for the existing hybrids and varieties and will be helpful for developing genomic studies and DNA fingerprinting for pearl millet hybrids and varieties.…”
Section: Molecular Characterization and Ssr Analysissupporting
confidence: 84%
“…It has been proved that SSRs can be suitable and efficient tool for molecular characterization of many plant species including pearl millet. Similarly, clustering between genotypes of pearl millet based on molecular markers was also recorded in other studies [11,17,[44][45][46].…”
Section: Diversity Analysis and Dendrogram Constructionsupporting
confidence: 73%
See 2 more Smart Citations
“…Interestingly, our results corroborate with earlier studies; for example, Sehgal et al (2015) reported that there were six subpopulations within these PMiGAP by using 345 entries of the PMiGAP and 37 SSR markers. Similarly, population genomic analysis was carried out by Kanfany et al (2020) and reported that the pearl millet inbred lines derived from diverse geographic and agroecological features possessed five subgroups mostly following pedigree differences with different levels of admixture. They have also stated that high genetic diversity prevails in pearl millet, which is very useful in defining heterotic groups for hybrid breeding, trait mapping, and holds promise for improving pearl millet for yield and nutritional quality.…”
Section: Discussionmentioning
confidence: 99%